The Impact of ZIS, Corruption, And Education on Income Inequality in Developing Countries: A Case Study of Indonesia - Padjadjaran University, Cupian; Prinary, Verina Araminda; Effendy, Ramadhansyah Rayyan; Hapsari, Nabela (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
This research aims to explain and find out how much influence ZIS (Zakat, Infaq and Sadaqah), corruption and education have on income inequality in Indonesia. This research uses a saturated sample, with data sourced from data from the National Zakat Amil Agency (BAZNAS), Transparency International, Central Statistics Agency (BPS) and World Bank. The research uses quantitative and time series data, the time series data contains years from 2011 to 2022, with Stata 15 as a data processing tool and multiple linear regression as our method. The findings of this research show that ZIS has a negative and significant effect on income inequality. The corruption variable has a negative and significant effect on income inequality. The education variable has a positive and insignificant effect. In the coefficient of determination test, the data obtained was 93.06% which could be explained by ZIS, corruption and education, while the remaining 6.94% could be explained by the influence of other variables not examined by the author. Furthermore, the research results show that ZIS and corruption jointly influence income inequality.